INFORMATION INTERACTION OF THERMOCHEMICAL POTENTIALS IN LIVING ORGANISMS AND GENERAL THEORY OF RELATIVITY - Tydnjuk, Volodymyr; Kravchenko, Volodymyr; Mul, Olena; Shut, Mykola (International Journal of Computing, 2014)
The application of general theory of relativity for building of model of living organisms field is considered. The information field, which connects living organism with environment, forms a material object of such field. A non- electromagnetic nature of such material object is substantiated. The phenomenon of interaction of thermochemical potentials at distance is investigated.